Prison conditions and recidivism - Francesco Drago; Roberto Galbiati; Pietro Vertova (Institute for the Study of Labor (IZA), 2008)
We use a unique data set on post-release behavior of former Italian inmates to estimate the effect of prison conditions on recidivism. By combining different sources of data we exploit variation in prison conditions measured by: 1) the extent of overcrowding at the prison level, 2) the number of deaths in the facility of detention during an inmate's stay and 3) the distance of the prison from the chief town of the province where the prison is located. By considering inmates who served their sentence in a jurisdiction different from the hometown in which they live after release, we can include province of residence fixed effects and account for the main source of unobserved heterogeneity correlated to prison conditions. We find that a harsher prison treatment does not reduce former inmates' criminal activity. The extent of overcrowding and the number of deaths do not decrease the probability to be re-arrested. Instead, we find evidence that the degree of isolation measured by distance from the prison of detention to the chief town of the province where the prison is located increases recidivism.
Keywords: K42; 360; Crime; prison; deterrence; Strafvollzug; Straftäter; Verhalten; Kriminalität; Kriminalpolitik; Italien